Safety and feasibility of urological procedures in Jehovah's Witness patients. (12th October 2021) - Han, Jullet; Ahmadi, Hamed; Ladi‐Seyedian, Seyedeh‐Sanam; Clifford, Thomas G; Douglawi, Antoin; Xu, Willem; Bazargani, Soroush T; Mingo, Samuel; Thangathurai, Duraiyah; Daneshmand, Siamak; Djaladat, Hooman
Abstract : Objectives: To describe the safety and feasibility of urological transfusion‐free surgeries in Jehovah's Witness patients. Methods: An institutional review board‐approved, retrospective review of Jehovah's Witness patients who underwent urological transfusion‐free surgeries between 2003 and 2019 was carried out. Surgeries were stratified into low, intermediate and high risk based on complexity, invasiveness and bleeding potential. Patient demographics, perioperative data and clinical outcomes are reported. Results: A total of 161 Jehovah's Witness patients (median age 63.4 years) underwent 171 transfusion‐free surgeries, including 57 (33.3%) in low‐, 82 (47.9%) in intermediate‐ and 32 (18.8%) in high‐risk categories. The mean estimated blood loss increased with risk category at 48 mL (range 10–50 mL), 150 mL (range 50–200 mL) and 388 mL (range 137–500 mL), respectively ( P  < 0.001). Implementing blood augmentation and conservation techniques increased with each risk category (3.5% vs 29% vs 69%, respectively; P  < 0.001). Average length of stay increased concordantly at 1.6 days (range 0–12 days), 2.9 days (range 1–13 days) and 5.6 days (range 2–12 days), respectively ( P  ≤ 0.001). However, there was no increase in complication rates and readmission rates attributed to bleeding among the risk categories at 30 days ( P  = 0.9 and 0.4, respectively) and 90 days ( P  = 0.7 and 0.7, respectively). Conclusions: Transfusion free urological surgery can be safely carried out on Jehovah's Witness patients using contemporary perioperative optimization. Additionally, these techniques can be expanded for use in the general patient population to avoid short‐ and long‐term consequences of perioperative blood transfusion.